On the origin of the electrical response of vapor grown carbon nanofiber + epoxy composites - Silva, J. (2012)
The origin of the electrical response of vapor grown carbon nanofiber (VGCNF) + epoxy composites is investigated by studying the electrical behavior of VGCNF with resin, VGCNF with hardener and cured composites, separately. It is demonstrated that the onset of the conductivity is associated to the emergence of a weak disorder regime. It is also shown that the weak disorder regime is related to a hopping depending on the physical properties of the polymer matrix.